Experimental evaluation of influence factors on wear and materials compatibility of the parts of the extruder - Войтов, В.А.; Цимбал, Б.М. (Problems of Tribology, 2016)
The paper presents an experimental evaluation of the negative impact of active acidity pH, abrasion and wear bur-den on speed, strength and friction material compatibility of working parts the extruder for the production of fuel pellets from plant material. Tribology investigated surface friction pairs steel and iron depending on the active acidity and abrasiveness and formed a theory about the mechanism of wear.